Saturn from Cassini-Huygens - Dougherty, Michele; Esposito, Larry; Krimigis, Stamatios (Springer Netherlands : Imprint: Springer, 2009)
This book reviews our current knowledge of Saturn featuring the latest results obtained by the Cassini-Huygens mission. A global author team addresses the planet's origin and evolution, internal structure, composition and chemistry, the atmosphere and ionosphere, the magnetosphere, as well as its ring system. Furthermore, Saturn's icy satellites are discussed. The book closes with an outlook beyond the Cassini-Huygens mission. Colorfully illustrated, this book will serve as a reference to researchers as well as an introduction for students.